The role of personal factors in 'Communication Mobility' development of Thai and Russian professionals in BELF context - Marina, Olga; Krich Rajprasit, (Penerbit Universiti Kebangsaan Malaysia, 2016)
With the aim of attempting to attain particular communicative goals, Communication Mobility (CM) can be viewed as one of the key elements in the complex construct of professional communicative competence in terms of oral English proficiency. CM has been proposed as an ability to employ a set of specific communicative strategies to facilitate professional communication, particularly among non-native English speakers. This preliminary study aims to identify perceived CM levels among Thai and Russian professionals working in international companies; to investigate possible correlation between personal factors (i.e. age, work experience, their perceived level of oral English proficiency, frequency of their attendance at meetings conducted in English, and frequency of English usage in their workplace) and CM; to compare these factors and the conditions in which CM may be developed among these two groups; and to predict the possibility of the development of CM. A quantitative method was employed and responses to the specifically designed questionnaire were obtained from 60 participants. The findings revealed that Russian participants were rated as very good users of CM, while Thai participants were only rated as fair CM users. In general terms, for both groups, only the frequency of English language use in the workplace was found to correlate with the perceived CM. The frequency of English language use in their workplaces was the only factor for the Thai participants to predict the development of CM. Such findings help in designing ESP courses which attempt to simulate workplace communicative situations, often seen as problematic and uncertain.